O compliance program e a sua efetividade nas empresas do segmento de papel e celulose - Mallmann, Paulo Sérgio Viana (Universidade do Vale do Rio dos Sinos, 2020)
The theme of this dissertation is compliance and its effectiveness in pulp and paper industry. This research about compliance aims to analyze the emergence of the idea in Brazil, its theoretical foundations established on foreign law and its actual application by the major companies in the pulp and paper industry. The main objective of this dissertation is to verify the effectiveness of the compliance programs applied through bibliography research, a set of questions submitted to these companies about the situation of some indicators, before and after its implantation, and the exam of the content of the compliance codes in the largest pulp and paper companies. The application of the programs was measured, both in terms of the internal aspects, as well as the external effects, in the relationship with various sectors of the society, notably customers, employees, suppliers, public agents and shareholders. The result of the research with collected data, inspite of the difficulties for obtaining the information requested, indicated a pale application of compliance principles in the sector, without decrease of the selected indicators, and the necessity of a larger engagement of the Public Authority, as advisor and formulator of improvement in the legal framework regarding this subject.
Keywords: Efetividade; Questionário; Indicadores; Setor de papel e celulose; Compliance; Effectiveness; Quiz; Indicators; Pulp and paper industry; ACCNPQ::Ciências Sociais Aplicadas::Direito